2021
DOI: 10.1016/j.envexpbot.2020.104294
|View full text |Cite
|
Sign up to set email alerts
|

Gypsum-exclusive plants accumulate more leaf S than non-exclusive species both in and off gypsum

Abstract: Gypsum-exclusive species (gypsophiles), are restricted to gypseous soils in natural environments. However, it is unclear why gypsophiles display greater affinity to gyspeous soils than other soils. These plants are edaphic endemics, growing in alkaline soils with high Ca and S. Gypsophiles tend to show higher foliar Ca and S, lower K and, sometimes, higher Mg than non-exclusive gypsum species, named gypsovags. Our aim was to test if the unique leaf elemental signature of gypsophiles could be the result of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Recent research suggests that knowledge of plant ionome is a key aspect to globally understand the ecosystems of the Earth [ 77 , 78 ]. Much of the research has been focused on this aspect in serpentine plants (e.g., [ 79 , 80 ]) and gypsum (e.g., [ 72 , 81 ]). Attention has been focused on several elements, often considered key, and on their ratios.…”
Section: Dolomitophily and Other Ca:mg Edaphismsmentioning
confidence: 99%
“…Recent research suggests that knowledge of plant ionome is a key aspect to globally understand the ecosystems of the Earth [ 77 , 78 ]. Much of the research has been focused on this aspect in serpentine plants (e.g., [ 79 , 80 ]) and gypsum (e.g., [ 72 , 81 ]). Attention has been focused on several elements, often considered key, and on their ratios.…”
Section: Dolomitophily and Other Ca:mg Edaphismsmentioning
confidence: 99%
“…these distantly related floras. This pattern could ultimately link to a nutritional specialization of gypsophiles to gypseous soils (Cera et al, 2020). Some gypsum endemic species have also been shown to have a higher ability than co-occurring gypsovags to surpass the hard physical crust typical of gypsum soils at the seedling stage (Romão and Escudero, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown how widely distributed gypsophiles from Spain (Palacio et al, 2014, 2007) and the Chihuahuan Desert (Muller et al, 2017) frequently share an ability to accumulate S and Ca in their leaves, which points at a convergent evolution towards similar adaptive traits in plants from these distantly related floras. This pattern could ultimately link to a nutritional specialization of gypsophiles to gypseous soils (Cera et al, 2020). Some gypsum endemic species have also been shown to have a higher ability than co-occurring gypsovags to surpass the hard physical crust typical of gypsum soils at the seedling stage (Romão and Escudero, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Gypsum specialist species differ from generalist species in their foliar S, Ca and Mg concentrations Merlo et al 2019), but not in their leaf P and N (Muller et al 2017;Sánchez-Martín et al 2021). In addition, plants growing on gypseous soils show low foliar P concentrations (Cera et al 2021). Previous studies analysed the differences in AMF colonisation between gypsum specialist and generalist species.…”
Section: Introductionmentioning
confidence: 99%